2021
DOI: 10.3390/ijerph182212146
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 and Trust in the Healthcare System Mediates the Association between Individual’s Risk Perception and Preventive COVID-19 Behaviours among Iranians

Abstract: Problems caused by the novel coronavirus disease-2019 (COVID-19) and its mutations have brought challenges in pandemic control for all countries worldwide. The present study examines the mediating roles of fear of COVID-19 and trust in the healthcare system in the association between individual’s risk perception and performing preventive COVID-19 behaviours among Iranians. A cross-sectional study design was used to collect data from 3652 residents of Qazvin province in Iran from 3 February to 15 April 2021 usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 33 publications
4
32
0
Order By: Relevance
“…Further studies are needed to examine the factors that mediate the association between other COVID-19-related variables and COVID-19 vaccine acceptance. These findings are not entirely new as some studies have also examined and established similar relationships between some COVID-19-related variables [32][33][34][35]44].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Further studies are needed to examine the factors that mediate the association between other COVID-19-related variables and COVID-19 vaccine acceptance. These findings are not entirely new as some studies have also examined and established similar relationships between some COVID-19-related variables [32][33][34][35]44].…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, adolescents' perceived stress from COVID-19 was associated with mental health problems (e.g., depression and sleep disorders) and other COVID-19-related variables such as fear of COVID-19 [30][31][32]. Other studies have also examined the relationships between some COVID-19-related variables [33][34][35]. Therefore, it can be deduced that COVID-19-related variables such as fear of COVID-19, believing COVID-19 information, and COVID-19 stress may be related to each other.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges posed by COVID-19 continues unabated [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] . One of the most efficient ways of controlling this pandemic is by vaccination.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Risk Perception and the Intention to Engage in Self-Protective Behaviors During the epidemic, scholars conducted extensive research on why people reacted differently to the epidemic, 17,18 and what factors affected their protection intention and protective behaviors. [19][20][21][22][23][24][25] Study suggested that protective behaviors were influenced by real or perceived risk. A lower perceived risk led to lower adherence to the intention to engage in protective behaviors, and a better understanding of higher risk perception led to higher possibilities of protective behaviors.…”
Section: Introductionmentioning
confidence: 99%